2018
DOI: 10.1590/1806-9282.64.01.54
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference in adolescents and cardiometabolic risk: A sistematic review

Abstract: There is a shortage of studies with representative samples, variety at the NC measurement sites, and the age of the participants, which makes it difficult to establish definitive landmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…In obese Mexican adolescents, the waist-to-hip ratio was superior in identifying cardio-metabolic risk factors [35] but in larger samples, BMI and WC performed better [27,36]. Recently, neck and wrist circumferences have emerged as useful measures in demonstrating the central distribution of fat; however, they could only serve as an alternative, as the predictive potential is still undetermined [37,38]. There is a criticism regarding WC in that it does not allow the quantification of adipose tissues, nor does it distinguish visceral fat from subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In obese Mexican adolescents, the waist-to-hip ratio was superior in identifying cardio-metabolic risk factors [35] but in larger samples, BMI and WC performed better [27,36]. Recently, neck and wrist circumferences have emerged as useful measures in demonstrating the central distribution of fat; however, they could only serve as an alternative, as the predictive potential is still undetermined [37,38]. There is a criticism regarding WC in that it does not allow the quantification of adipose tissues, nor does it distinguish visceral fat from subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%
“…There is a criticism regarding WC in that it does not allow the quantification of adipose tissues, nor does it distinguish visceral fat from subcutaneous fat. Also, there is no standardized method for measuring WC or defined reference values for children and adolescents [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that NC has moderate accuracy for identifying overweight and obesity in children and adolescents. [ 20 , 21 ] However, some studies have questioned the validity of NC for determining obesity and central obesity in children. [ 26 , 27 ] Several expected findings give confidence to our data:…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 , 19 ] However, 2 recent meta-analyses/systematic reviews have reported that NC has moderate accuracy for identifying overweight and obesity in children and adolescents, although the issues of standardization of measurements and cut-off values by age and gender remain. [ 20 , 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Upper-body subcutaneous fat estimated by neck circumference (NC) may be linked to a higher metabolic risk than abdominal visceral fat. NC is a simple, convenient but less used anthropometric measure correlated with waist circumference (WC) and body mass index (BMI) and has been associated with components of metabolic syndrome in cross-sectional [8][9][10] and cohort studies [11][12]. NC may likely be a very convenient and valid alternative measure of obesity and may even be a better marker of metabolic risk than standard measures such as BMI and WC [9].…”
Section: Introductionmentioning
confidence: 99%